2017
DOI: 10.1016/j.bbabio.2017.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial transition ROS spike (mTRS) results from coordinated activities of complex I and nicotinamide nucleotide transhydrogenase

Abstract: Mitochondria exhibit suppressed ATP production, membrane potential (∆Ψ) polarization and reactive oxygen species (ROS) bursts during some cellular metabolic transitions. Although mitochondrial ROS release is influenced by ∆Ψ and respiratory state, the relationship between these properties remains controversial primarily because they have not been measured simultaneously. We developed a multiparametric method for probing mitochondrial function that allowed precise characterization of the temporal relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Nevertheless, the capability of ROS production at both low and high rates of ETC activity highlights the complex nature of ROS production under different conditions. Recently, simultaneous measurement of oxygen consumption, Δψ m and ROS production showed that at low Δψ m and high ETC activity, ROS levels were low, but a transient ROS increase occurred when switching to a state of low ETC activity [50]. In summary, at both low ETC flux (high pmf) and high ETC flux (low pmf) there is potential for ROS production, but under most circumstances, increasing ETC flux decreases ROS (Fig.…”
Section: Mitochondrial Reactive Oxygen Species Productionmentioning
confidence: 96%
See 3 more Smart Citations
“…Nevertheless, the capability of ROS production at both low and high rates of ETC activity highlights the complex nature of ROS production under different conditions. Recently, simultaneous measurement of oxygen consumption, Δψ m and ROS production showed that at low Δψ m and high ETC activity, ROS levels were low, but a transient ROS increase occurred when switching to a state of low ETC activity [50]. In summary, at both low ETC flux (high pmf) and high ETC flux (low pmf) there is potential for ROS production, but under most circumstances, increasing ETC flux decreases ROS (Fig.…”
Section: Mitochondrial Reactive Oxygen Species Productionmentioning
confidence: 96%
“…Accelerated ETC activity increases the volume of electrons flowing, which could increase the probability of ROS production [40]. Experimentally, ROS formation at high ETC rates can be observed when ROS scavenging pathways are overwhelmed [50], but under physiologic conditions these pathways maintain ROS homeostasis [40]. Further, it has been recently shown that ROS levels in cells are more dependent upon rates of mitochondrial ROS production than they are to cellular ROS scavenging rates [51].…”
Section: Mitochondrial Reactive Oxygen Species Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the free (15,131,207) and enzyme-bound states of reduced flavins (78,130,131) are known to produce ROS on oxidation with molecular oxygen. Importance of the NADH/NAD + ratio for E3-catalyzed ROS production links the ROS generated by the 2-oxo acid dehydrogenase complexes at a high NADH to the NADHdependent production of NADPH by nicotinamide nucleotide transhydrogenase, a protein of the inner mitochondrial membrane, which is crucial for redox homeostasis (137,163,171). Obviously, in vivo utilization of NADH in the transhydrogenase reaction would not only increase the disulfide reductant NADPH but also decrease NADH available for the backward side reaction of E3 yielding ROS.…”
Section: B Catalysis By 2-oxo Acid Dehydrogenase Complexes Is Tightlmentioning
confidence: 99%